1998
DOI: 10.1080/096381898336402
|View full text |Cite
|
Sign up to set email alerts
|

Reinventing auditing, redefining consulting and independence

Abstract: This paper deals with recent developments in auditing, taking KPMG's 'business measurement process' as its example. From this example it is discussed how and why auditing is currently being 'reinvented'. The 'reinvention' of auditing, it is argued, represents a fundamental break with the established epistemological dualism between auditing and management advisory services,1 that is central to most literature on auditor independence, including the European Commission's Green Paper. Consequently, it is not only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 4 publications
2
90
0
1
Order By: Relevance
“…Discourses seeking to redefine and market auditing in consulting terms also took place in the West, in the 1980s and early 1990s, particularly before the Enron scandal (see e.g. Jeppesen, 1998;Robson et al, 2007). Yet differently from the West, in Russia discourses about consulting emerged at the same time when auditing was introduced, and not as something that was added on to audit.…”
Section: Changing Relations Between Politics and Expertisementioning
confidence: 99%
See 2 more Smart Citations
“…Discourses seeking to redefine and market auditing in consulting terms also took place in the West, in the 1980s and early 1990s, particularly before the Enron scandal (see e.g. Jeppesen, 1998;Robson et al, 2007). Yet differently from the West, in Russia discourses about consulting emerged at the same time when auditing was introduced, and not as something that was added on to audit.…”
Section: Changing Relations Between Politics and Expertisementioning
confidence: 99%
“…(Bukhgalterskii uchet, 1998, No. 8, p. 8) A shift is articulated from socialist inspection to Western-oriented business consulting (see also Baklan, 1988;Pyatenko, 1998Pyatenko, , 2001 (Hinings et al, 1999;Jeppesen, 1998;Robson et al, 2007), the "added value" of their services to potential clients.…”
Section: Doctors Who Healmentioning
confidence: 99%
See 1 more Smart Citation
“…Hopwood (1996), Jeppesen (1998) and Humphrey and Moizer (1990) observed that much of audit and its associated technologies remained a 'black box'. Cooper and Robson (2006, p. 240) emphasised the value of knowing how professional audit works, and how "competence and skill [are] constructed and reproduced across countries".…”
Section: Justification For the Researchmentioning
confidence: 99%
“…They demonstrated that many authors (Beattie et al, 2001;Humphrey, 2008;Power, 2003) have strongly criticised the current approach to audit research, which is predominantly quantitative and focused on testing the validity of hypotheses which, as Gendron (2006) pointed out, are often removed from the realities of auditors' practice. Commentators have criticised current audit research as having accomplished little in bridging the knowledge gap in 'audit technologies' (Hopwood, 1996;Humphrey & Moizer, 1990;Jeppesen, 1998), and critiqued the ways in which professional audit work, competence and skill are constructed and reproduced across countries (Cooper & Robson, 2006).…”
Section: Contributions To Qualitative Audit Researchmentioning
confidence: 99%